ChemInform Abstract: Synthesis of Trifluoromethylated Isoxazolidines: 1, 3‐Dipolar Cycloaddition of Nitrosoarenes, (Trifluoromethyl)diazomethane, and Alkenes. Issue 47 (4th November 2013) - Molander, Gary A.; Cavalcanti, Livia N.
Abstract Additionally a one‐pot procedure for the cycloaddition reaction followed by reductive ring cleavage (Zn/AcOH) is described.